2022
DOI: 10.1186/s12885-022-10038-z
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation of transient receptor potential melastatin-related 7 (TRPM7) predicts a better prognosis in patients with Luminal A breast cancers

Abstract: Breast cancer is the most common female tumors arising worldwide, and genetic and epigenetic events are constantly accumulated in breast tumorigenesis. The melastatin-related transient receptor potential 7 channel (TRPM7) is a nonselective cation channel, mainly maintaining Zn2+, Ca2+ and Mg2+ homeostasis. It is also involved in regulating proliferation and migration in various cancers including breast cancer. However, epigenetic alterations (such as promoter methylation) of TRPM7 and their correlation with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…A recent study has demonstrated that TRPM7 was highly expressed in the luminal A subtype of breast cancer. Nevertheless, the promoter methylation of TRMP7 was associated with a better prognosis of the disease [160].…”
Section: Breast Cancermentioning
confidence: 96%
“…A recent study has demonstrated that TRPM7 was highly expressed in the luminal A subtype of breast cancer. Nevertheless, the promoter methylation of TRMP7 was associated with a better prognosis of the disease [160].…”
Section: Breast Cancermentioning
confidence: 96%
“…In xenografts, immunodeficient Rag2−/−IL2rg−/− mice, harboring human MDA‐MB‐231 cells, these high TRPM7 levels were required for cancer proliferation and metastasis ( 294 ). More recently, it has been described that the increased expression of TRPM7 channels predicts reduced survival in patients suffering from Luminal A breast cancer ( 295 ). The authors found that the methylation frequency of the channel has a mean of 42.7% in the whole cohort, while it is much lesser in Luminal A cancer versus other subtypes (33.3% vs. 45.7% in Luminal B, 46.9% in Her2+, and 51.3% in Basal-like).…”
Section: Trpm Channels: Characteristics and Functionsmentioning
confidence: 99%
“…In breast cancer, TRPM7 is associated with poor prognosis, cell migration and metastasis [ 67 , 68 ], and its high methylation profile is associated with a good prognosis [ 69 ]. However, its role in cell proliferation is not completely clear, as it seems to highly contribute to the proliferation of the adenocarcinoma cell line MCF7 [ 70 ] but not the triple-negative breast cancer cell line MDA-MB-231 [ 71 ].…”
Section: Mechanoreceptors In Cancermentioning
confidence: 99%